Organo Phosphorus–Selenium Heterocycles Derived from Haloalkanols and Alkenes - Hua, Guoxiong; Fuller, Amy L.; Slawin, Alexandra M. Z.; Woollins, J. Derek (Synlett, 2012)
Treating Woollins’ reagent with an equimolar amount of sodium 2-bromoalkanolates (which were prepared in situ from the reaction of bromoalkanol and NaH) in THF gave five- or six-membered PSeOCn (n = 2 or 3) phosphorus–selenium heterocycles 3 and 4 in good yields. Woollins’ reagent reacting with one equivalent of conjugated 1,3-dienes led to the formation of different end products: with 1,4-diphenylbuta-1,3-diene giving a five-membered 2,3,5-triphenyl-4-styryl-1,2,5-selenadiphospholane 2,5-diselenide; however, with 2,3-dibenzyl-1,3-butadiene affording 4,5-dibenzyl-2-phenyl-3,6-dihydro-2H-1,2-selenaphosphinine 2-selenide as a major isolable product. Refluxing Woollins’ reagent with one equivalent of unconjugated 2,5-dimethyl-1,5-hexyldiene in toluene produced P–Se heterocyclic compound 3-methyl-3-(3-methylbut-3-en-1-yl)-2,5-diphenyl-1,2,5-selenadiphospholane 2,5-diselenide with the same five-membered C2P(Se)SeP(Se) motif as 2,3,5-triphenyl-4-styryl-1,2,5-selenadiphospholane 2,5-diselenide. Furthermore, heating a toluene solution of Woollins’ reagent with an equimolar amount of N-allylaniline gave rise of a five-membered C2NP(Se)Se heterocycle 5-methyl-2,3-diphenyl-1,3,2-selenazaphospholidine 2-selenide; carrying out a reaction of cinnamonitrile with an equivalent of Woollins’ reagent under identical conditions did not give any air-stable product, however, 3-phenylprop-2-eneselenoamide was isolated in 95% yield after treatment with water. Three demonstrative X-ray structures are reported.
Keywords: Woollins’ reagent; phosphorus–selenium heterocycles; alkenes; haloalkanols; selenoamide